Prevalence of four statin benefit groups in a population of the Caribbean region of Colombia (2019)
Objectives: To estimate the prevalence of four Statin Benefit Groups (SBG) according to the 2018 ACC/AHA Multisociety Guideline on the Management of Blood Cholesterol, in a population of the Caribbean region of Colombia enrolled to DTC program Mutual SER-EPS in 2015 Methods: Data on a history of hyperlipidemia was collected by study investigators at including adults patients enrolled to DTC program Mutual SER-EPS in 2015 (N = 64,667) with ICD-10 diagnosis of hyperlipidemia (E78), or with a personal history of hyperlipidemia; or with abnormal lipid profile; or patients under treatment with lipid-lowering drugs. The four SBG were comprised adult patients $21 years of age with clinical atherosclerotic cardiovascular disease (ASCVD) (SBG1); adults $21 years of age with LDL-C $190 mg/dL (not due to secondary modifiable causes) (SBG2); adults aged 40 to 75 years without ASCVD, but with diabetes and with LDL-C 70 to 189 mg/dL (SBG3); and adults ages 40 to 75 years without ASCVD or diabetes, with LDL-C 70 to 189 mg/dL, and an estimated 10-year risk for ASCVD of $ 20% as determined by the Framingham Risk Score (SBG4). The prevalence of statin use by SBG and factors associated with statin use were estimated. Results: The prevalence of SBG1, SBG2, SBG3 and SBG4 in patients enrolled to DTC program Mutual SER-EPS in 2015 were 4.6% (2,985), 0.5% (337), 2.5% (1,633) and 1.3% (891), respectively. The prevalence of statin use in SBG1, SBG2, SBG3 and SBG4 were 69.1% (2,064), 40.6% (137), 47% (768) and 59.1% (463), respectively. Arterial hypertension (OR: 2.70; 95% IC 1.70-4.28) and personal history of ASCVD (OR: 3.43; 95% IC 2.15-5.46) were very significantly associated with statin use. Conclusions: The prevalence of SBG and statin use in patients enrolled to DTC program Mutual SEREPS in 2015 were 9% (5,846) and 58.7% (3,432), respectively.